Pengaruh Ekstrak Bit Merah (Beta vulgaris L.) Terhadap VEGF, dan Ketebalan Endometrium Pada Tikus (Rattus norvegicus) Dipapar Asap Rokok - Dahlan, Zulfa Hanum; Dewita, Dewita (Window of Health : Jurnal Kesehatan, 2018)
Exposure to cigarette smoke often occurs among people, especially low-income countries. Frequent exposure to cigarette smoke can cause an increase in ROS in the body resulting in increased oxidative stress. As a result of ROS increases the antioxidants in the body decreases, therefore it takes antioxidants from the outside contained in food sources, one red bit. Red bits contain betalain compounds that are high in antioxidants that function to neutralize ROS in the body. This study aims to determine the effect of red beet ethanol extract with various doses to increase the expression of VEGF, and thickness in endometrium of mice exposed to cigarette smoke. The research design is True Experiments with Post Control Only Control Group Design design. The study used 25 female rats divided into 5 groups: negative control group, positive control, treatment I, II and III. The dose of bit extract used was PI (125 mg/kgBW/day), PII (250 mg/kgBW/day), PIII (500 mg/kgBW/day). The data were analyzed using One Way Anova with p-value VEGF (p = 0.000), and p-value of thickness endometrium (p = 0.000). The results showed that administration of red beet ethanol extract at doses of 500 mg/kgBW/day increased the expression of VEGF, and endometrial thickness of mice exposed to cigarette smoke. Keywords: Exposure to cigarette smoke, VEGF Expression, Endometrial Thickness, Red Beet.